Seasonal environmental factors drive microbial community succession and flavor quality during acetic acid fermentation of Zhenjiang aromatic vinegar - Ye, Xiaoting; Yu, Yongjian; Liu, Jiaxin; Zhu, Yuanyuan; Yu, Zhen; Liu, Peng; Wang, Yuqin; Wang, Ke (Frontiers in Microbiology, 2024)
This study investigated the impact of seasonal environmental factors on microorganisms and flavor compounds during acetic acid fermentation (AAF) of Zhenjiang aromatic vinegar (ZAV). Environmental factors were monitored throughout the fermentation process, which spanned multiple seasons. Methods such as headspace solid phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS), high performance liquid chromatography (HPLC), and high-throughput sequencing were employed to examine how these environmental factors influenced the flavor profile and microbial community of ZAV. The findings suggested that ZAV brewed in autumn had the strongest flavor and sweetness. The key microorganisms responsible for the flavor of ZAV included Lactobacillus acetotolerans, Lactobacillus plantarum, Lactobacillus reuteri, Lactobacillus fermentum, Acetobacter pasteurianus. Moreover, correlation analysis showed that room temperature had a significant impact on the composition of the microbial community, along with other key seasonal environmental factors like total acid, pH, reducing sugar, and humidity. These results provide a theoretical foundation for regulating core microorganisms and environmental factors during fermentation, enhancing ZAV quality.